Disrupting aetonormativity: involving children in the writing of literature for publication. (2nd January 2021) - Dobson, Tom; Stephenson, Lisa; De Arede, Ana
ABSTRACT: Literary criticism of children's literature asserts a one-directional view of power with the adult writer constructing the child reader. Using "aetonormativity"– adult perceptions of normality – this paper explores what happens when children co-construct publishable fiction. Our analysis of drama and creative writing workshops shows how whilst we were interested in developing the story of the protagonist, the children wanted to develop a gaming narrative. As a community of writers, we constructed a "hybrid" text which, unlike GameLit, explores the relationship between the protagonist and gaming, whilst providing positive portrayal of gaming. As the children became invested in the fiction, they became editors and revisions were taken on board. The paper concludes that involving children in writing children's literature can result in texts which disrupt aetonormativity by representing lived experiences. The paper also acknowledges that that further research is needed to explore how other children respond to such texts.